Isolation and purification of Eleutherococcus sessiliflorus (Rupr. & Maxim.) S. Y. Hu peptides and study of their antioxidant effects and mechanisms - Liu, Chang; Ding, Xuying; Xie, Yining; Chen, Chen; Zhao, Meijun; Duan, Yanming; Yuan, Guojing; Ren, Junxi (Frontiers in Pharmacology, 2024)
Oxidative stress is a state of imbalance between oxidative and antioxidant effects in the body, which is closely associated with ageing and many diseases. Therefore, the development of antioxidants has become urgent. In this study, we isolated three polypeptides, G-6-Y, P-8-R and F-10-W, from Eleutherococcus sessiliflorus (Rupr. & Maxim.) S. Y. Hu (E. sessiliflorus), based on the antioxidant and anti-aging properties of Eleutherococcus, and screened the most powerful free radical scavenging peptide P-8-R. Ultraviolet B (UVB)-induced oxidative stress damage in the skin was established to test the efficacy of P-8-R. In cellular experiments, P-8-R not only prevented oxidative stress damage in HaCaT cells, reduced intracellular ROS levels, inhibited the overexpression of matrix metalloproteinases (MMPs), but also inhibited apoptosis via the mitochondria-dependent apoptotic pathway; in animal experiments, P-8-R was able to prevent oxidative stress damage in the skin and reduce skin collagen loss by inhibiting the overexpression of MMPs to prevent mouse skin aging. In conclusion, the present study contributes to the in-depth understanding of the active compounds of Eleutherococcus, which is of great significance for the pharmacodynamic mechanism and industrial development of Eleutherococcus, and P-8-R is likely to become a potential antioxidant and anti-aging drug or skin care cosmetic in the future.